Nilai Susut Masak Daging Ayam Broiler yang diberi Pakan Herbal Berupa Kunyit - Khaeriyah Nur; Anita Sari (Musamus Journal of Livestock Science, 2020)
This study aims to determine the value of cooking losses in broiler meat with herbs feed of turmeric. The research was conducted at the Animal Husbandry Department, Pangkajene Islands State Agricultural Polytechnic Campus. The research design used a completely randomized design (CRD) with a unidirectional pattern with 3 treatments and 4 replications. Each replication consisted of 8 chickens. The treatment arrangements were P0 = conventional feeding and drinking water (control); P1 = Mixing turmeric into feed; P2 = Mixing turmeric in drinking water. The maintenance stage is carried out for approximately 30 days, feed and drink are given ad libitum, and no vaccination program is carried out. Sampling was carried out at the age of approximately 30 days. A total of 12 chickens were taken randomly from each treatment and processed into carcass. In the test, the breast sample was weighed before and after cooking the meat, then the cooking losses were calculated by looking at the difference. The results of the analysis of variety showed that there was no significant effect (P> 0.05) on the value of meat cooking loss between treatments. Average cooking losses range from 2-4%. The sample of P1 treatment broiler meat had the best quality of carcass quality because it had the lowest cooking loss value. The addition of turmeric to broiler chicken feed can help improve carcass quality by absorbing more optimal nutrients from the meat.